Dasar Perekonomian Indonesia Dalam Pentimpanan Mandat Konstitusi UUD Negara Tahun 1945 - Ruslina Elli (Total Media, 2013)
Dasar Perekonomian Indonesia Dalam Pentimpanan Mandat Konstitusi UUD Negara Tahun 1945